The Migration Dynamics and public policies in the state of Espírito Santo - Dota, Ednelson Mariano; Nascentes Coelho, André Luiz; Mangaba de Camargo, Danilo (Guará Journal, 2018)
This paper discusses the migratory movements that impacted the State of Espírito Santol throughout the 2000s and were captured by the brasilian demographic census of 2010. In order to achieve the ob-jectives of disseminating easily accessible data to the community in a simple and accessible way, a set of indicators and an atlas, in the digital format, were elaborated at the municipality level, whose spa-tial data allow to establish relations with other dynamics of the con-temporary society and at other levels of analysis. The results showed that there are large variations in migration among the regions of the State, possibly associated with the main economic activities of each area and the outcome of the current processes, highlighting the im-portance of considering migration in the planning of municipal and regional public policies